Multi-subject implementation method based on web development framework - XIE YING; WU YUYAN (2016)
The invention provides a multi-subject implementation method based on a web development framework and belongs to the technical field of web application development. In the same application, a directory is created according to a directory rule provided by the framework, a static resource file needed by a page needing personalized display or a personalized page is re-defined under the directory, and personalized display of different regions for individual pages is achieved. The development and maintenance cost is minimum while the personalized display requirements of different regions for the individual pages are met. 本发明提供种基于web开发框架的多主题实现方法，属于web应用开发技术领域，本发明在同个应用程序中，通过按照框架提供的目录规则建立目录，并在该目录下重新定义需要个性化展示的页面或个性化页面所需要的静态资源文件，实现不同地区对个别页面的个性化展示。能够在满足不同地区对个别页面个性化展示需求的同时，使开发及维护成本最小化。